ChemInform Abstract: 2‐Pyrrolecarbaldiminato—Cu(II) Complex Catalyzed Three‐Component 1, 3‐Dipolar Cycloaddition for 1, 4‐Disubstituted 1, 2, 3‐Triazoles Synthesis in Water at Room Temperature. Issue 25 (5th June 2015) - Zhou, Changjian; Zhang, Jie; Liu, Ping; Xie, Jianwei; Dai, Bin
Abstract: 2‐Pyrrolecarbaldiminato—Cu(II) complexes are highly efficient catalysts for the one‐pot three‐component cycloaddition of various benzyl halides with alkyl/aryl acetylenes/acetylene gas, and NaN3 leading to 1, 4‐disubstituted 1, 2, 3‐triazoles with high regioselectivity.